INVESTIGATING THE INFLUENCE OF STUDENT IDENTITIES ON SENSE OF COMMUNITY IN ONLINE LEARNING COMMUNITIES - Nasir, Nur Azlinda Kasma Azizan Kamal Abdul (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores the relationship between students’ identities and their sense of community in the context of online learning among undergraduate students at Malaysian public universities. It investigates whether students’ professional and learner identities influence their level of connectedness within online learning environments. Adopting a correlational research design and Structural Equation Modeling (SEM) analysis with a sample of 367 students, data were collected using the Students’ Identities Questionnaire and the Classroom and School Community Inventory (CSCI). The findings indicate that while students demonstrate strong professional and learner identities, these identities do not significantly influence their sense of community. The study suggests that efforts to foster a sense of community in online learning should emphasize social interaction and inclusive engagement strategies rather than focusing solely on individual identity traits. The implications highlight the importance of lecturer facilitation and institutional support in building meaningful connections among students in virtual learning spaces.